Untargeted adductomics of newborn dried blood spots identifies modifications to human serum albumin associated with childhood leukemia. (January 2020) - Yano, Yukiko; Schiffman, Courtney; Grigoryan, Hasmik; Hayes, Josie; Edmands, William; Petrick, Lauren; Whitehead, Todd; Metayer, Catherine; Dudoit, Sandrine; Rappaport, Stephen
Highlights: Untargeted adductomics was used to analyze 782 archived newborn dried blood spots. HSA-Cys34 modifications were compared between childhood leukemia cases and controls. T-cell ALL had higher abundances of adducts of reactive carbonyl species. A Cys34 adduct of homocysteine discriminated between AML cases and controls. Abstract: The developing fetus is exposed to chemicals, which are metabolized to electrophiles that form adducts with nucleophilic Cys34 of human serum albumin (HSA). By measuring these adducts in neonatal blood spots (NBS), we obtain information regarding fetal exposures during the last month of gestation. To discover potential risk factors for childhood leukemia resulting from in utero exposures, we used untargeted adductomics to measure HSA-Cys34 adducts in 782 archived NBS, collected from incident cases of childhood acute lymphoblastic leukemia (ALL) or acute myeloid leukemia (AML) and matched population-based controls. Among a total of 28 Cys34 modifications that were measured, we found no differences in adduct abundances between childhood leukemia cases and controls overall. However, cases of T-cell ALL had higher abundances of adducts of reactive carbonyl species and a Cys34 disulfide of homocysteine was present at lower levels in AML cases. These results suggest that oxidative stress and lipid peroxidation may be etiologic factors of T-cell ALL, and alterations in one-carbon metabolism and epigenetic changes may be predictors of AML. Future replication of the results with larger sample sizes is necessary.